2011
DOI: 10.1124/dmd.110.037317
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of P-Glycoprotein (ABCB1) and Breast Cancer Resistance Protein (ABCG2) on Axitinib Brain Accumulation and Oral Plasma Pharmacokinetics

Abstract: ABSTRACT:The second-generation tyrosine kinase inhibitor and anticancer drug axitinib is a potent, orally active inhibitor of the vascular endothelial growth factor receptors 1, 2, and 3. Axitinib has clinical activity against solid tumors such as metastatic renal cell carcinoma and advanced pancreatic cancer. We studied axitinib transport using Madin-Darby canine kidney II cells overexpressing human ABCB1 or ABCG2 or murine Abcg2. Axitinib was a good substrate of ABCB1 and Abcg2, whereas transport activity by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 36 publications
5
46
2
Order By: Relevance
“…Our finding that axitinib is at most only a weak substrate for MDR1 and not a BCRP substrate is in contrast to the recent publication by Poller et al (2011), which identified axitinib as a good and moderate substrate for MDR1 and BCRP, respectively. We found that, over a concentration range of axitinib from 1 to 5 mM, the P-gp mediated efflux ratio in the MDR1-MDCK was #1.45, and our positive control substrate, digoxin, exhibited an efflux ratio of 24.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Our finding that axitinib is at most only a weak substrate for MDR1 and not a BCRP substrate is in contrast to the recent publication by Poller et al (2011), which identified axitinib as a good and moderate substrate for MDR1 and BCRP, respectively. We found that, over a concentration range of axitinib from 1 to 5 mM, the P-gp mediated efflux ratio in the MDR1-MDCK was #1.45, and our positive control substrate, digoxin, exhibited an efflux ratio of 24.…”
Section: Discussioncontrasting
confidence: 56%
“…It is possible that axitinib is a substrate for canine P-gp and that the MDR1-MDCK and BCRP-MDCK cell lines used by Poller et al (2011) may contain higher levels of canine P-gp than our cell lines, resulting in the contrasting results between the two laboratories. Additionally, it was previously demonstrated that P-gp activity differs between species (Tang-Wai et al, 1995).…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations